How Should American Students Understand their Civic Culture? The Continuing Battle over the 2002 Massachusetts History and Social Science Curriculum Framework - Sandra Stotsky (Universidad de Navarra, 2018)
I write as the former administrator in the Massachusetts Department of Education who was responsible for the development of the 2002 Massachusetts History and Social Science Curriculum Framework. This essay is a slightly revised version of written testimony invited by Senator Judd Gregg of New Hampshire, Chairman of the Committee on Health, Education, Labor and Pensions, United States Senate, for a hearing titled "What Is Your Child Reading in School? How Standards and Textbooks Influence Education." The hearing was held at the Dirksen Senate Office Building, Room 430, Washington, D.C., on Wednesday, September 24, 2003. The oral testimony is available on a transcription of the hearing, and the full written version of my testimony has been entered into the public record. The hearing was an exploratory one, possibly the first of many others on this topic, and unconnected at the moment to any proposed legislation.